Germalna, a new genus for the New Caledonian cicada previously assigned to the genus Melampsalta Kolenati, plus a complement to the description of the genus Rouxalna Boulard, with the description of two new species (Insecta: Hemiptera, Cicadoidea, Cicadidae) - Delorme, Quentin (Zootaxa, 2018)
Species previously assigned to Melampsalta Kolenati, in New Caledonia are reviewed. Morphological studies indicate that New Caledonian cicadas currently placed in this genus have been wrongly assigned and should be placed in a new genus. The genus Germalna gen. nov., is therefore erected to accommodate Germalna germaini comb. nov. The genus Germalna gen. nov. was first documented by Michel Boulard, but remained a nomen nudum until now. A redescription of the genus Rouxalna Boulard is provided and the following new species are described: Rouxalna villosa sp. nov., and Rouxalna scabens sp. nov. Male calling songs of Rouxalna rouxi Boulard and Rouxalna scabens sp. nov. are analysed and described from field recordings. A key to the species of Rouxalna is also provided.